Progress towards the 95–95–95 targets to end HIV by 2030 in Lebanon, 2023 - Mohammed Gouda ElMedrek; Joumana Hermez; Yvan Hutin; Abdinasir Abubakar; Ghada Muhjazi; Emmanuel Olatunji; Muhammad Shahid Jamil; Ahmed Sabry Alaama; Nevin Wilson; Firass Abiad; Hiam Yaacoub; Mostafa El Nakib (PLoS ONE, 2025)
Background Lebanon faces an HIV epidemic concentrated in key populations. The national AIDS programme [NAP] hosted by WHO since 1989 achieved substantial progress towards the 95-95-95 UNAIDS targets. In 2023, we reviewed the programme to guide its planned transition back into the structure of the Ministry of Health [MOH]. Methods In 2023, we reviewed programme documents, epidemiological information and interviewed relevant stakeholders. We compiled national data along with WHO and UNAIDS estimates to describe the evolution of programme and epidemiological indicators, along with the result chain of input, process, output, outcome and impact. Results Domestic funding for the NAP increased from 73% in 2007 to 97% in 2018, before a drop in 2019 because of the financial crisis, when the NAP became dependent on international funding, including the Global Fund (commodities and services) and WHO (human resources). NAP core functions were governance, capacity building, monitoring and evaluation, anti-retro viral treatment [ART] dispensing and follow up for persons living with HIV [PLHIV] with some involvement in procurement, supply chain and laboratory testing. The NAP provided prevention, diagnosis and treatment services through Civil Society Organizations [CSOs]. In 2022, in Lebanon, 86% of PLHIV were diagnosed, among which 93% were on treatment and 95% virally suppressed. In 2022, NAP reported 232 new HIV infections, a 41% increase since 2010 and a 25% decrease in AIDS-related deaths during the same period. The estimated HIV incidence increased 4.4 times among MSM from 2008 to 2019, remained zero among commercial sex workers, and evolved from 0 to 0.11 per 1,000 to 0.9 per 1,000 in 2021 among PWIDs. Conclusions Lebanon is on track to achieve the UNAIDS 95-95-95 by 2025 targets. After transition into the MoPH, the NAP will need to [1] identify ways to sustain its sources of domestic funding, [2] build on its collaborations with CSOs to expand prevention activities in key populations, and [3] address the evolving needs of the population, including among transgenders, migrants, displaced people, and refugees, 4) maintain good quality core functions (capacity building, monitoring and evaluation, and medications).